CAPITAL AND INCOME ANALYSIS IN WHOLESALE BUSINESS UD. RIZKI JAYA - Amru Usman; Raisa Salsabila; Sara Yulis; Farica Yusrina Lubis; Cut Safani; Rafsanjani Rafsanjani (PT. Radja Intercontinental Publishing, 2023)
Development era which modern also participate give impact positive with development industry trade, one of which is in the field of wholesale trade. UD shop. Rizki Jaya one of the grocery stores that opened because of the creative desire of the shop owner, namely Pak Syaiful, to create jobs as well as income to fulfill daily life. The purpose of this study is to determine the effect of capital business on the success of the store, as well as knowing an increase in the income of UD Grocery Stores. Rizky Jaya. The research was conducted using quantitative and qualitative methods. Data collection, as well as subsequent interviews observations will be made. UD shop. Rizki Jaya has carried out Management Aspects, namely planning, supervision, marketing strategy, and financial management. Capital has a big influence on business developmentand the success of UD Stores. Rizky Jaya. There is an increase in UD Shop revenue. Rizki Jaya, improvement is influenced by the interests of the community. It is necessary to make improvements to the implementation of aspects of management by shop owner UD. Rizki Jaya, especially in the aspect of supervision, as well as the form of report writing, must be more detailed in Ledger so cash flow can be pictured well.